(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The study aimed to identify the basic climatic factors that significantly affect wheat production during the period from 2000 to 2022 to draw up a clear agricultural policy to confront these changes. Statistical tests were conducted to ensure the existence of a balanced long-term relationship between the impact of climate changes on wheat production in Iraq using the ARDL model to clarify the correlation between the dependent variable (production) and the independent variables temperature, rainfall, and relative humidity. And wind speed. The research reached several conclusions, the most important of which is that 99% of the observed fluctuations in the dependent variable can be attributed to the explanatory variables included in the model. The remaining 1% of fluctuations are due to other variables not included in the model and are absorbed by the random variable. The results showed a positive and significant relationship between average rainfall and wheat yield and a significant inverse relationship between temperature, relative humidity, and average wind speed on wheat crops. The study suggested the necessity of cultivating high-yielding varieties that are resistant to climate change and suitable for the Iraqi environment, making optimal use of water resources, and developing economic policies that consider adaptation to climate change. In addition, she stressed the importance of investing in renewable energy sources that can support agricultural activities, mitigate the effects of climate change, and enhance crop productivity.